Independent Commissioners and Tax Avoidance: The Role of Sustainability - Kennardi Tanujaya; Felicia; Robby Krisyadi (Balance Vocation Accounting Journal, 2026)
This study aims to investigate how independent commissioners influence corporate tax avoidance, using sustainability performance as a mediating variable, and to examine whether independent commissioners encourage responsible tax practices through enhanced sustainability engagement. The research was conducted in Indonesia using secondary data from companies listed on the Indonesia Stock Exchange during the period 2019–2023, employing a quantitative approach with regression analysis and path analysis for mediation testing using Stata software. The results show that independent commissioners have a positive and significant impact on sustainability performance by enhancing corporate transparency and accountability, while their direct effect on tax avoidance is insignificant. However, sustainability performance significantly reduces tax avoidance and mediates the relationship between independent commissioners and tax avoidance. These findings indicate that independent commissioners indirectly encourage responsible tax behavior through improved sustainability practices, suggesting the need to strengthen governance frameworks and sustainability disclosure standards to promote ethical corporate behavior. The study is limited to a specific period (2019–2023) and the Indonesian context, which may reduce the generalizability of the findings to other regions or timeframes, but it contributes to the corporate governance and sustainability literature by providing empirical evidence on the mediating role of sustainability performance in Indonesia and offering insights for researchers, policymakers, and companies regarding the role of board independence in encouraging ethical tax practices.